Assessment of the Knowledge of Occupational Hazards and Safety Practices among Healthcare Workers in Police Hospital, Accra, Ghana - Duodu, F. (University of Ghana, 2018)
Background Healthcare staff work in an environment considered to be one of the most hazardous occupational settings. This is especially true in developing countries where health service delivery is fraught with inadequate protection against exposures to numerous fomites and pathogens. Studies have shown that inadequate knowledge of occupational hazards and unavailability of safety measures contribute greatly to the increased incidence of occupational accidents and injuries among healthcare workers (HCWs). However, there is limited research on knowledge of occupational hazards and safety measures among HCWs of the Ghana Police. Objective This study examined knowledge of occupational hazards and safety practices among healthcare workers of Ghana Police Hospital, Accra. Methods A descriptive cross-sectional survey involving 216 randomly sampled HCWs was conducted. Data was collected using validated standardized questionnaire and analysed using descriptive statistics and multivariate analysis of covariance (MANCOVA) and linear regression with the help of STATA version 15. Results Findings of the study showed that the participants recorded high level of knowledge of biological (93.5%), moderate level of knowledge of psychosocial hazards (84%) and ergonomic hazards (82%) and low level of physical (72%) and chemical hazards (66.5%). Control measures provided by employers recorded highest (96%) level of knowledge, University of Ghana http://ugspace.ug.edu.gh xiv followed by individual protective practices (82.5%) and then institutional culture and practices (79.2%). Age, educational level, income level and profession had significant effect (P < 0.05) on knowledge of psychosocial, chemical and ergonomic hazards. Conclusion Even though control measures had been instilled to minimize occupational hazards, accidents, injury and death, some institutional lapses were identified that need to be addressed to strengthen safety practices and improve occupational health. The findings of the study are expected to help improve awareness on occupational hazards among healthcare workers and promote safety practices at the work environment.
MA.
Keywords: Occupational Hazards; Healthcare; Accra; Ghana